The Love Israel Family: urban commune, rural commune - LeWarne, Charles P. (Univ. of Washington Press, 2009)
The beginnings -- Prologue -- Paul Erdmann becomes Love Israel -- The urban commune -- Living together -- The spiritual focus -- A community in the community -- Foes and friends in the larger world -- Stretching outward -- The breakup -- Flies in the ointment -- Breaking up is hard to do -- Picking up the pieces -- The rural commune -- Entrepreneurial ventures -- The people and their lives -- Unraveling toward bankruptcy